Perancangan Sistem Informasi Penjualan dan Pengecekan Resi pada PT. Syahid Husada Dewata berbasis Web - Alifi, Gastiadirrijal Fikas; Putra, I Putu Arya Permana; Agustino, Dedy Panji (JATISI, 2024)
PT Syahid Husada Dewata has several obstacles that affect sales operations. Some of these obstacles include the process of ordering medical devices still using conventional methods via whatsapp and email to the admin and the absence of features such as checking receipts that allow customers to track the delivery status of their orders in real-time. Therefore, PT Syahid Husada Dewata requires the development of an integrated information system in the hope of solving the above obstacles significantly for the company. This research will use the waterfall method, system design using Data Flow Diagram (DFD), database design in the form of Entity Relationship Diagram (ERD) and Conceptual Database, and intuitive and responsive interface design. The results of this research are expected to streamline the business processes carried out by PT Syahid Husada Dewata so that they can solve several obstacles that affect sales operations and strengthen their business position compared to other companies.